Deteksi Resistensi Isolat Bakteri Salmonella sp. dari Feses Segar Ayam Petelur (Gallus gallus domesticus) terhadap Antibiotik - Widia Restu; Candra Dwi Atma; Yeti Kurniasih; Kholik Kholik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Antibiotic resistance is a global problem that connects human and animal health. This resistance occurs when bacteria acquire genes that allow them to survive when exposed to antibiotics. Wanasaba District, East Lombok is one of the districts that has a large population of laying hens, one of the infectious diseases that often attacks poultry and is treated using antibiotics is salmonella sp. This study aims to detect the resistance of Salmonella sp. bacterial isolates derived from fresh feces of laying hens (Gallus gallus domesticus) to antibiotics. This study is a laboratory experimental study conducted in November 2025 with a total of 3 samples of fresh feces of laying hens taken using a purposive sampling method. Bacterial isolation was carried out using Xylose Lysine Deoxycholate (XLD) agar media, then identified using biochemical tests to confirm the presence of Salmonella sp. Antibiotic resistance tests were carried out using the Kirby-Bauer disc diffusion method using 30 μg tetracycline antibiotics, 10 μg gentamicin, and 5 μg enrofloxacin. The results showed that all Salmonella sp. isolates from the three samples demonstrated 100% sensitivity to the three types of antibiotics tested. These results indicate that Salmonella sp. isolates in laying hens at the study site have not yet developed resistance to the antibiotics used. However, monitoring antibiotic use and implementing good farm management are still necessary to prevent the emergence of bacterial resistance in the future.